Topical application of honey in the management of radiation mucositis: a randomized trial - Biswal, Biswa Mohan; Zakaria, Ahmad; Ahmad, Nik Min (2001)
Radiation induced mucositis is a very common morbidity among head and neck cancer patients during radiotherapy. The intensity of mucositis varies according to different treatment parameters and can be reduced by physical and pharmacological intervention.This is a randomised trial to evaluate the efficacy of topical natural honey to prevent radiation mucositis.Forty diagnosed cancer patients requiring radiation to the head and neck area were randomised to receive radiation alone or radiation plus topical application of pure natural honey.Patients were treated using a 6-MV linear accelerator,at a dose rate of 2 Gy per day treating 5-times a week up to a dose of 60-70 Gy.In the study arm, patients were advised to take 20 millilitres of pure honey 15 minutes before,15 minute after,and 6 hours post radiation therapy.Patients were evaluated every week for the development of radiation mucositis using RTOG grading system.The study was conducted between November 2000 and October 2001.There was significant reduction in the symptomatic grade-3/4 mucositis among honey treated patients compared to controls; i.e. 20% versus 75% (p0.00058).The maximum intensity of mucositis was observed towards 3rd weeks of radiotherapy on both arms.The compliance of honey treated group of patients was better than controls.Fifty five percent(55%) of patients treated with topical honey showed no change or positive gain of body weight compared to 25% in the control arm (p0.053).In conclusion,topical application of natural honey is a simple and cost-effective treatment In radiation mucositis,which need further multi centre randomised trials to validate our finding.